2013
DOI: 10.1073/pnas.1214880110
|View full text |Cite
|
Sign up to set email alerts
|

Fossil slabs attached to unsubducted fragments of the Farallon plate

Abstract: As the Pacific–Farallon spreading center approached North America, the Farallon plate fragmented into a number of small plates. Some of the microplate fragments ceased subducting before the spreading center reached the trench. Most tectonic models have assumed that the subducting oceanic slab detached from these microplates close to the trench, but recent seismic tomography studies have revealed a high-velocity anomaly beneath Baja California that appears to be a fossil slab still attached to the Guadalupe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 34 publications
4
75
1
Order By: Relevance
“…The geometry is consistent with the hypothesis that the San Andreas Fault in central California soles into the top of the stalled Monterey Microplate, a remnant of the subducted Farallon Plate that was captured by the Pacific Plate [35][36][37] . If so, the offset LFE families may be generated by strike slip on the shallowly dipping interface between the stalled slab and the North American Plate.…”
Section: Tremor Migration Patterns and Fault Zone Complexitysupporting
confidence: 77%
See 1 more Smart Citation
“…The geometry is consistent with the hypothesis that the San Andreas Fault in central California soles into the top of the stalled Monterey Microplate, a remnant of the subducted Farallon Plate that was captured by the Pacific Plate [35][36][37] . If so, the offset LFE families may be generated by strike slip on the shallowly dipping interface between the stalled slab and the North American Plate.…”
Section: Tremor Migration Patterns and Fault Zone Complexitysupporting
confidence: 77%
“…In particular, LFE sources south of Parkfield that are offset up to 10 km northeast from the main trend perhaps hint at the presence of a fossil Farallon slab remnant at the base of the crust. If so, then the mantle San Andreas Fault zone may be deflected eastward along the slab surface, as some have proposed [35][36][37] . Future work should endeavour to constrain the sense of slip of these offset sources, which would further inform the configuration of the San Andreas beneath the crust.…”
mentioning
confidence: 96%
“…Previous studies (Zhang et al 2009;Wang et al 2013) interpret the high-velocity anomaly beneath west-central Baja as a fossil slab and this is also justified by the distribution of the post-subduction volcanism in the area. In our study, this feature is not as laterally continuous, nor does it cover as large an area as that observed by Wang et al (2013), although we note that their map extends further westwards than ours. We follow their interpretation of this feature as a stalled remnant of the Guadalupe and/or Magdalena microplates since this feature persists at depths of ∼60 to ∼110 km (Figs 9 and 12).…”
Section: Discussionmentioning
confidence: 98%
“…A relatively highvelocity anomaly was also found by Zhang et al (2009) at depths between 120 and 160 km. Considering the distribution of volcanic rocks in Baja, Wang et al (2013) interpret this fast velocity anomaly as a fossil slab attached to the unsubducted Magdalena microplate. The fast velocity zone is also evident in the east-west profiles in Fig.…”
Section: Results: Shear Wave Velocity Mapsmentioning
confidence: 99%
“…It appears to have fragmented into several smaller east-dipping plate segments (Wang et al 2013 (Ingersoll 1978(Ingersoll , 1979(Ingersoll , 1983Linn et al 1992 A few pre-Mesozoic, multicycle grains were reported from basal GVG sandstones by DeGraaff- Surpless et al (2002) and Wright and Wyld (2007). These zircon ages provide Precambrian peaks at 1,000-1,200, 1,400, 1,800-2,000, and 2,600 Ma, suggesting that minor ultimate sources including the Grenville, Mazatzal-Yavapai, and Wyoming or Superior provinces.…”
Section: Hypothesized Klamath Salient Displacement Mechanismmentioning
confidence: 96%